Cloud Packets Forensics through NIDS and NIPS with Honeypot - VK, Bhanushree; Minavathi (International Journal of Computer Sciences and Engineering, 2020)
As of today, almost everyone currently relocating their administrations into the cloud to offer an increasingly adaptable, open, versatile and omnipresent assistance. In any case, this additionally carries more introduction to security dangers, digital assaults and troubles in dependability and wellbeing. The proposed arrangement is to send a Honeypot in the Intrusion Detection and Prevention System (IDPS) model so as to ensure upgraded execution, extended degree of security in the Distributed computing condition and decrease in the threats to the Cloud condition - by concentrating on the issue of how the information is stored in the Cloud. The structure depicted utilizations both Anomaly Detection (AD) and Signature Detection (SD) in coordinated effort, to recognize various assaults and deny them access using the proposed IPS. The goal of this report is to feature, perceive and ensnare inward interlopers by the utilization of the Honeypot